The C‐terminal α‐helix of YsxC is essential for its binding to 50S ribosome and rRNAs. Issue 16 (21st June 2015) - Wicker-Planquart, Catherine; Ceres, Nicoletta; Jault, Jean-Michel
Abstract : YsxC is an essential P‐loop GTPase that interacts with the 50S subunit of the ribosome. The putative implication in ribosome binding of two basic clusters of YsxC, a conserved positively charged patch including R31, R116, H117 and K146 lying adjacent to the nucleotide‐binding site, and the C ‐terminal alpha helix, was investigated. C ‐terminal truncation variants of YsxC were unable to bind to both ribosome and rRNAs, whereas mutations in the other cluster did not affect YsxC binding. Our results indicate that the basic C ‐terminal region of YsxC is required for its binding to the 50S ribosomal subunit. Abstract : Mutations in YsxC conserved positively charged patch do not affect 50S YsxC binding. YsxC‐R31A and YsxC‐R116A strongly bind both 30S and 50S ribosomal subunits. The YsxC C ‐terminal region of YsxC is essential for YsxC binding to 50s ribosome.